Das Schloß - Haneke, Michael,Mühe, Ulrich,Eisermann, André,Lothar, Susanne (1997)
K. kommt als vom
Fernsehmitschnitt: 3SAT 12.12.2007
Keywords: DVD-Video; Kafka; Franz; Das Schloss; Literatur; Verfilmung; Fernsehsendung